Педагогічний потенціал освітнього процесу у формуванні мовно-комунікативної компетентності майбутніх учителів початкових класів - Кучай Тетяна; Kuchai Tatiana; Kucsáj Tetjána (Видавництво «Код», 2024)
Резюме. У статті розкрито педагогічний потенціал освітнього процесу у формуванні мовнокомунікативної компетентності майбутнього вчителя. Встановлено що він є резервом освітнього простору і проявляється в поетапному створенні мотиваційно-когнітивної, операційно-діяльнісної, ціннісно-рефлексивної сфер мовно-комунікативної компетентності у процесі рефлексії здобувача в умовах міжкультурної комунікації. Визначено структуру особистісного потенціалу вчителя. Досліджено можливості педагогічного потенціалу освітнього процесу у формуванні мовно-комунікативної компетентності майбутнього вчителя початкових класів.

Abstract. The article reveals the pedagogical potential of the educational process in the formation of language and communicative competence of the future teacher. It has been established that it is a reserve of educational space and is manifested in the step-by-step creation of motivational-cognitive, operational-activity, value-reflective spheres of language-communicative competence in the process of reflection of the acquirer in the conditions of intercultural communication. The structure of the personal potential of the primary school teacher is determined: qualification, psychophysiological, educational, creative, communicative and moral potentials. The possibilities of the pedagogical potential of the educational process in the formation of linguistic and communicative competence of the future primary school teacher were investigated. The issue of realizing the pedagogical potential of the educational process in the formation of linguistic and communicative competence of future primary school teachers is revealed. It is proved that the project is a work independently planned and implemented by the winners, in which speech communication is woven into the intellectual and emotional context of their communicative and cognitive activity. The connection of the project with a specific educational and communicative situation has been established. The properties of the educational and communicative situation are revealed. It has been established that the main one in the triad of means of formation of linguistic and communicative competence is dialogue. The essence of dialogue is revealed as a special linguistic and communicative environment containing a mechanism for the formation and self-justification of an individual in the conditions of a plurality of cultures. Methods of determining the level of formation and dynamics of mastering linguistic and communicative competence are proposed. It has been proven that the pedagogical potential of the educational process in the combination of opportunities, abilities, and resources ensures the productivity of the formation of language and communicative competence of the future teacher, as it allows to create a motivational-cognitive, operational-active, value-reflective basis of this competence in the process of enriching the individual language experience of the acquirer in the conditions of intercultural communication, the structural components of which (cognitive experience, metacognitive experience, intentional experience) are the addressees of pedagogical influences; to develop the subjectivity of the future teacher as a result of changing the forms of subject-subject interaction (from prompting to action to self-organized action); to transform and complicate the character of learners' cognitive activity (from reproductive to heuristic to the learners' construction of their own creative language activity) when using a triad of learning tools (dialogue of cultures, educational and communicative situations, projects).
Pedagogical potential of the educational process in forming language and communicative competence of future teachers of primary classes
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00015039 Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-10
Keywords: педагогічний потенціал; освітній процес; формування; мовнокомунікативна компетентність; суб᾿єкт-суб᾿єктна взаємодія; комунікація; майбутні учителі; початкові класи